Trypanosome KKIP1 Dynamically Links the Inner Kinetochore to a Kinetoplastid Outer Kinetochore Complex - Brusini, Lorenzo; D’Archivio, Simon; McDonald, Jennifer; Wickstead, Bill (Frontiers in Cellular and Infection Microbiology, 2021)
Kinetochores perform an essential role in eukaryotes, coupling chromosomes to the mitotic spindle. In model organisms they are composed of a centromere-proximal inner kinetochore and an outer kinetochore network that binds to microtubules. In spite of universal function, the composition of kinetochores in extant eukaryotes differs greatly. In trypanosomes and other Kinetoplastida, kinetochores are extremely divergent, with most components showing no detectable similarity to proteins in other systems. They may also be very different functionally, potentially binding to the spindle directly via an inner-kinetochore protein. However, we do not know the extent of the trypanosome kinetochore, and proteins interacting with a highly divergent Ndc80/Nuf2-like protein (KKIP1) suggest the existence of more centromere-distal complexes. Here we use quantitative proteomics from multiple start-points to define a stable 9-protein kinetoplastid outer kinetochore (KOK) complex. This complex incorporates proteins recruited from other nuclear processes, exemplifying the role of moonlighting proteins in kinetochore evolution. The outer kinetochore complex is physically distinct from inner-kinetochore proteins, but nanometer-scale label separation shows that KKIP1 bridges the two plates in the same orientation as Ndc80. Moreover, KKIP1 exhibits substantial elongation at metaphase, altering kinetochore structure in a manner consistent with pulling at the outer plate. Together, these data suggest that the KKIP1/KOK likely constitute the extent of the trypanosome outer kinetochore and that this assembly binds to the spindle with sufficient strength to stretch the kinetochore, showing design parallels may exist in organisms with very different kinetochore composition.